Highly sensitive nano-aerosol detection based on the whispering-gallery-mode in cylindrical optical fiber resonators. Issue 12 (1st December 2016) - Wang, Dong; Wang, Zihan; Lee, Aram; Marr, Linsey C.; Heflin, James R.; Xu, Yong
ABSTRACT: Highly sensitive detection of nanoscale aerosols, or nano-aerosols, is a difficult challenge. Here, we report a fiber optical technique that is capable of detecting trace-level nano-aerosols. Our method is based on monitoring the nano-aerosol-induced resonance shift due to the optical Whispering-Gallery-Mode (WGM) in a cylindrical optical fiber resonator. A nearly linear relationship between the WGM resonance shift and the aerosol coverage ratio of silica nanoparticles (40–50 nm dia.) on the fiber resonator was identified in the low coverage regime. Our experimental results imply sensitivity at the level of ∼2 nanoparticles per μm 2 deposited on the fiber resonator, which corresponds to pg-level sensitivity in the total aerosol mass within the effective detection area. The response of this fiber optical sensor is further confirmed by using silica nanoparticles deposited on the fiber surface via electrostatic self-assembly. The fiber optical technique for nanoparticle detection may ultimately lead to an instrument capable of real-time in situ aerosol detection with ultrahigh sensitivity. Copyright © 2016 American Association for Aerosol Research